Analysis of The Physical Quality of Coffee Husk Compost with The Addition of EM4 Bioactivator - Sugeng Prayitno Harianto,; Tsani, Machya Kartika; Surnayanti,; Trio Santoso, (Journal of Sylva Indonesiana, 2023)
Coffee production potential is matched by waste from grinding coffee cherries. However, the coffee cherry peel (husk) is rich in essential nutrients for plant growth, including potassium, phosphorus, and nitrogen. Therefore, the purpose of this research was conducted to determine the physical quality of coffee husk compost given the addition of EM4 bioactivator. This study consisted of 2 treatments and 4 replications, namely control (coffee husk + sawdust + goat manure) and EM4 (coffee husk + sawdust + goat manure + EM4). Observations were made every 3 days until the compost was ripe with the parameters of temperature, humidity, color, smell, and texture. The results showed that the entire coffee husk compost had matured within 36 days and exhibited physical characteristics according to SNI 19-7030-2004. According to the matured compost speed, treatment with mixing compost materials using EM4 shows a faster time than without EM4. In addition, the addition of EM4 gives better results in terms of texture, color, and smell compared to compost without EM4